Neighbors' use of water and sanitation facilities can affect children's health: a cohort study in Mozambique using a spatial approach - Berta Grau-Pujol; Jorge Cano; Helena Marti-Soler; Aina Casellas; Emanuele Giorgi; Ariel Nhacolo; Francisco Saute; Ricard Giné; Llorenç Quintó; Charfudin Sacoor; Jose Muñoz (BMC, 2022)
Abstract Background Impact evaluation of most water, sanitation and hygiene (WASH) interventions in health are user-centered. However, recent research discussed WASH herd protection - community WASH coverage could protect neighboring households. We evaluated the effect of water and sanitation used in the household and by household neighbors in children's morbidity and mortality using recorded health data. Methods We conducted a retrospective cohort including 61,333 children from a district in Mozambique during 2012-2015. We obtained water and sanitation household data and morbidity data from Manhiça Health Research Centre surveillance system. To evaluate herd protection, we estimated the density of household neighbors with improved facilities using a Kernel Density Estimator. We fitted negative binomial adjusted regression models to assess the minimum children-based incidence rates for every morbidity indicator, and Cox regression models for mortality. Results Household use of unimproved water and sanitation displayed a higher rate of outpatient visit, diarrhea, malaria, and anemia. Households with unimproved water and sanitation surrounded by neighbors with improved water and sanitation high coverage were associated with a lower rate of outpatient visit, malaria, anemia, and malnutrition. Conclusion Household and neighbors' access to improve water and sanitation can affect children's health. Accounting for household WASH and herd protection in interventions' evaluation could foster stakeholders' investment and improve WASH related diseases control. Graphical Abstract Distribution of main water and sanitation facilities used during study period.